China-Algeria, a unique relationship in Africa. - (:unkn) unknown (My University, 2014)
Socialist Algeria had friendly relations with Maoist China; it is paradoxically during the 1990s and the 2000s, while Algeria abandoned the official reference to socialism, that economic, commercial and human relations between the two countries began experiencing an unprecedented expansion in such a way that it could feed fantasies about the Chinese presence and expectations in Algeria. This book examines the sudden acceleration of the relations between the two countries. It aims first at assessing the extent and outlines of these relations, then at putting this phenomenon into perspective relatively to what is taking place on the African continent; it therefore distinguishes casual aspects of this presence from those which may last more permanently, singular features from those which are more commonly met in Africa.
Keywords: African Research